Is wantokism a form of social capital? : comparative study of two communities in Oro Province, PNG : a thesis presented in partial fulfillment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Manuda, Tony (Massey University, 2007)
Social capital is an important prerequisite for development however the form it assumes is one which has to be understood well by development practitioners. A lot of interest in social capital has been generated recently particularly in the Pacific as social relations in between people and various societal institutions in these islands are in many ways influenced by ethno linguistic affiliations. Only when these relationships between development agents and beneficiaries are understood in their local context can one truly appreciate it as a form of social capital. Hence, the term 'wantokism' which relates to social relations between people sharing similar ethno linguistic ties becomes an interesting topic of discussion in especially in the heterogeneous Melanesian countries of the Pacific. This subject is discussed in this thesis through comparing social relations between actors in two separate communities in Papua New Guinea. The Buna community school project and Kokoda hospital project in the Oro Province of Papua New Guinea are examples of projects that involved a wide variety of people from all sectors of the community. The Kokoda project funded jointly by the Papua New Guinea and Australian government under the Australian War Graves office was successfully completed and is fully operational while the Buna project funded by the Japanese government under its Japanese International Cooperation Agency program was not completed. In a society where trust and cooperation among wantoks is expected to a higher degree this research explores this issue in both this projects and whether or not the lack of it or abundance in one may have contributed to its failure or success. Through consultation with project board members, community members, provincial and district government personnel at both these locations this research raises the question of whether there is trust and cooperation between project boards and the wider community prior to and during the project work. More importantly it raises the question of whether there is trust and cooperation on the basis of wantokism. This thesis shows that the strong bonding social capital inherent in wantokism is clearly exemplified in both communities. However, there was minimal trust among board members and the local community, and a lack of bridging social capital in particularly Buna which affected its ability to access resources from outside sources. In contrast, there was a higher level of bridging social capital, and better trust and cooperation between board members and the local community at Kokoda. Drawing together from firstly, a theoretical analysis of social capital, ethnicity and wantokism and secondly, from qualitative and quantitative research in these two communities, it reaches conclusions about the extent to which wantokism could be a form of social capital.
Keywords: Papua New Guinea; Social capital (Sociology); Sociolinguistics; Social life and customs